2012
DOI: 10.1002/qj.2053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of optical depth variability on contrail radiative forcing

Abstract: Line-shaped contrails arising from aircraft emissions affect radiative forcing. The magnitude of the radiative forcing from contrails depends strongly on their optical depth and their spatial and temporal variability caused by dynamical and microphysical processes. Here we investigate the significance of this variability, both for modelling contrail radiative forcing and estimating thresholds for the detection of contrails in satellite imagery. Ignoring the variability of contrail optical depth in models by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Vázquez-Navarro et al (2015) found larger mean values because their method mainly detects geometrically and optically thick contrails. The shape of the SW and LW RF pdfs is similar to theory predictions (Kärcher and Burkhardt, 2013), but negative RF values were not expected in that study.…”
Section: Contrail Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…Vázquez-Navarro et al (2015) found larger mean values because their method mainly detects geometrically and optically thick contrails. The shape of the SW and LW RF pdfs is similar to theory predictions (Kärcher and Burkhardt, 2013), but negative RF values were not expected in that study.…”
Section: Contrail Propertiessupporting
confidence: 85%
“…The pdf of log τ has a negative skewness: a few contrails thicken, while most have small τ , and some are subvisible. The same type of asymmetry in the pdf of log τ has been simulated by Kärcher and Burkhardt (2013) for contrails and measured by Immler et al (2008) for contrail cirrus. The global mean optical depth τ is 0.29, which is close to values observed for young contrails .…”
Section: Contrail Propertiesmentioning
confidence: 56%
“…Figure 6 also depicts the resulting model PDF of contrail OD and its cumulant, along with an observed cumulative PDF 56 . The model PDF derives from an analysis of satellite observations 66 and contains many optically thin and even invisible portions within contrails. This indicates that contrails that are non-detectable by passive remote sensing and invisible by ground-based observers may exert a non-negligible RF despite their low OD, since they are likely associated with large coverage 67 .…”
Section: Radiative and Climate Impactmentioning
confidence: 99%
“…The cumulative distribution function of optical depth  (near 550 nm) has a negative skewness, see Fig. 5: A few contrails get thick while most have small ; some are subvisible, and only the thicker ones are observable (Immler et al 2008;Kärcher and Burkhardt 2013).…”
Section: Optical Propertiesmentioning
confidence: 99%